TEXNOLOGIYA SABAQLARÍNDA OQÍWSHÍLARDÍŃ ROBOTOTEXNIKA BOYÍNSHA BILIM HÁM KÓNLIKPELERIN RAWAJLANDÍRÍW TENDENCIYALARÍ - Baltabaev, J.O.; Shamuratova, T.J.; Kamilova, M.K. (ILIM hám JÁMIYET, 2024)
This article presents information and recommendations on specific areas for developing the interests, knowledge and skills of students in robotics based on modern approaches in technology subjects in secondary schools. Work is also presented on career guidance for students in the field of robotics in classroom and extracurricular activities.